Effects of age, period, and cohort on the prevalence of frailty in Chinese older adults from 2002 to 2014 - Li, Siying; Fan, Wenye; Zhu, Boya; Ma, Chao; Tan, Xiaodong; Gu, Yaohua (Frontiers in Public Health, 2022)
Background Currently, longitudinal studies on frailty are in an early stage, particularly in low- and middle-income countries. Only one study was conducted in Hong Kong to examine age-period-cohort effects on the prevalence of frailty among Chinese older adults. Objectives This study aims to shed light on the prevalence trajectory of frailty among older adults in mainland China through the APC model and to analyze the effects of age, period, and cohort on the prevalence trajectory. Methods The sample for this study was older adults aged 65–109 years old from the 2002 to 2014 Chinese Longitudinal Healthy Longevity Survey (CLHLS). Frailty status was measured by Rockwood FI. An age-period-cohort model was used to describe the effects of age, period, and cohort on the prevalence trajectory of frailty. Results The prevalence of frailty among Chinese older adults changed significantly with age, period, and cohort. Furthermore, the effect of age was much stronger than the effect of period and cohort. The prevalence of frailty in the 101–103 and 104–106 age groups was 8.998 (95% CI 13.667–5.924) and 8.699 (95% CI 13.037–5.805) times higher than the in the 65–67 age group, respectively. The sensitivity analysis based on Fried's frailty phenotype showed similar results, confirming the robustness of our findings. Conclusion All of the age effect reflecting the individual aging process, period effect reflecting change in the social environment, and birth cohort effect reflecting different generations could influence the prevalence of frailty at the population level. In contrast, the age effect was the main effect.